On The Teaching Innovation of The Differential Equation Course for Engineering Students - zhao, shufen (JOURNAL OF ADVANCES IN MATHEMATICS, 2022)
This paper focuses on the teaching innovation of differential equation course for engineering students, and explores the innovative methods and ways of teaching mode, teaching content and teaching means in this course.